The beginning of language : opposing viewpoints - Swisher, Clarice (San Diego, Calif. : Greenhaven Press, 1989)
Discusses historical, philosophical, and scientific theories about the mysterious origins of human language.
Includes index.
Keywords: Language and languages; Language and languages